2009
DOI: 10.1108/09653560910938556
|View full text |Cite
|
Sign up to set email alerts
|

The role of knowledge management in post‐disaster housing reconstruction

Abstract: Purpose -A disaster is a serious disruption for the operation of a society, causing extensive life and property losses. Since construction activities are highly knowledge-intensive, knowledge management (KM) practices will encourage continuous improvement, distribute best practices, quick response to beneficiaries, share valuable tacit knowledge, reduce rework, improve competitiveness and innovations, and reduce complexities in post-disaster housing reconstruction. Therefore, this research aims to study and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…While housing is a critical concern in disaster recovery (Katz 2008;Thanurjan and Seneviratne 2009), the notion of home is a recent addition to the literature (Brun and Lund 2008;Chamlee-Wright and Storr 2009;Hawkins and Maurer 2011). As Morrice (2013: 33) indicates, "there has been a notable absence in geographic literature concerning the connection between disasters and the concept of 'home.'"…”
Section: Home: Making and Unmakingmentioning
confidence: 97%
“…While housing is a critical concern in disaster recovery (Katz 2008;Thanurjan and Seneviratne 2009), the notion of home is a recent addition to the literature (Brun and Lund 2008;Chamlee-Wright and Storr 2009;Hawkins and Maurer 2011). As Morrice (2013: 33) indicates, "there has been a notable absence in geographic literature concerning the connection between disasters and the concept of 'home.'"…”
Section: Home: Making and Unmakingmentioning
confidence: 97%
“…Conversely, the reduction of reworks ensures sustainable development, as less rework means that fewer materials are wasted [49]. Amaratunga et al [50] found that reducing reworks can highly improve the performance of reconstruction projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the facets of knowledge are seldom comprehended or distinguished in a context of disaster risk reduction. Nevertheless, a few academic studies recognize the potential benefits of effective knowledge exchange for disaster risk reduction and post-disaster recovery and have addressed different aspects that hinder the application in practice (Spiekermann et al 2015;Weichselgartner and Pigeon 2015;Thanurjan and Seneviratne 2009;Abedin and Shaw 2015). The value of knowledge exchange in post-disaster recovery lies in the ability of a community to learn from previous disasters and apply new skills to protect themselves.…”
Section: Knowledge Exchangementioning
confidence: 99%